Hereditary Susceptibility for Triple Negative Breast Cancer Associated With Western Sub-Saharan African Ancestry: Results From an International Surgical Breast Cancer Collaborative. Issue 3 (September 2019) - Newman, Lisa A.; Jenkins, Brittany; Chen, Yalei; Oppong, Joseph K.; Adjei, Ernest; Jibril, Aisha S.; Hoda, Syed; Cheng, Esther; Chitale, Dhananjay; Bensenhaver, Jessica M.; Awuah, Baffour; Bekele, Mahteme; et al.
Abstract : Objective: To investigate subtype-specific risk of germline alleles associated with triple negative breast cancer (TNBC) in African ancestry populations. Background: Breast cancer (BC) mortality is higher in African American (AA) compared to White American (WA) women; this disparity is partly explained by 2-fold higher TNBC incidence. Methods: We used a surgically maintained biospecimen cohort of 2884 BC cases. Subsets of the total (760 AA; 962 WA; 910 West African/Ghanaian; 252 East African/Ethiopian) were analyzed for genotypes of candidate alleles. A subset of 417 healthy controls were also genotyped, to measure associations with overall BC risk and TNBC. Results: TNBC frequency was highest in Ghanaian and AA cases (49% and 44% respectively; P < 0.0001) and lowest in Ethiopian and WA cases (17% and 24% respectively; P < 0.0001). TNBC cases had higher West African ancestry than non-TNBC ( P < 0.0001). Frequency of the Duffy-null allele (rs2814778; an African ancestral variant adopted under selective pressure as protection against malaria) was associated with TNBC-specific risk ( P < 0.0001), quantified West African Ancestry ( P < 0.0001) and was more common in AA, Ghanaians, and TNBC cases. Additionally, rs4849887 was significantly associated with overall BC risk, and both rs2363956 and rs13000023 were associated with TNBC-specific risk, although none as strongly as the Duffy-null variant. Conclusions: West African ancestry is strongly correlated with TNBC status, as well as germline variants related to BC risk. The Duffy-null allele was associated with TNBC risk in our cohort.